FROM TRADITION TO TREND: CRAFTING A DRESS SERIES WITH NATIONAL SATIN FABRICS - M.M. Ulugboboyeva (American Journals Publishing, 2023)
This scholarly article comprehensively explores the developmental trajectory of a dress collection crafted from indigenous satin fabric, examining its conceptual evolution and design progression. It delves into the intricate cultural significance and creative process behind utilizing national satin fabric as a central element in fashion design. Through a blend of empirical analysis and qualitative insights, the article elucidates the cultural, artistic, and historical influences that contributed to the conceptualization and creation of this dress collection. By tracing the journey from ideation to realization, the study sheds light on the fusion of traditional craftsmanship with contemporary design paradigms, offering insights into the intricate interplay between heritage textiles and modern fashion sensibilities. Additionally, it underscores the socio-cultural impact of promoting and preserving national fabric heritage within the context of fashion and design. Overall, this article serves as a valuable academic resource, providing in-depth exploration and analysis of the creative and cultural dimensions involved in developing a collection of dresses from a distinctive national satin fabric.
Keywords: Costume design, concept, deconstructivism, composition centre.